International Labour Standards Electronic Library - International Labour Organization (Geneva : International Labour Organization, 2011)
ILSE is an electronic reference library of basic ILO documents on In ternational Labour Standards. All documents are available in the three working languages of the ILO. A selection of further texts is available in other languages.
This CD contains the general report and individual comments from its 2011 report, pending observations from previous reports and discussion s of obervations that were examined by the conference committee on the application of standards at the International Labour Conference in 2010 .
ILO also includes documents in Arabic, Chinese, German, Portuguese a nd Russian.
Created by the Information and Communication Team of the Internation al Labour Standards Department based on documents in the ILOLEX databa se on International Labour Standards
Minimum system requirements: Ms windows 95, 12-speed CD-ROM driv. Br owser: Ms explorer 4.0 of netscape communicator 4.0 or higher. Sreen re solution: 800x600 pixels.
The information on this CD is in English, French and Spanish.
Keywords: Digital libraries; Data CD